Természetvédelmi kezelés gyepregenerációs eredményei a budapesti Homoktövis Természetvédelmi Területen (2009-2021) - Péter, Norbert; Bajor, Zoltán; Saláta, Dénes; Pápay, Gergely; Lisztes-Szabó, Zsuzsa; Stilling, Ferenc Tamás; Zimmermann, Zita; Penksza, Károly (Gyepgazdálkodási Közlemények, 2022)
In Budapest, despite the density of the population, precious plant communities still remain in a lot of, mostly isolated fragments of habitats which,are outstanding in the diversity of species and are rare inhabitants of endemic species. On the examined territory, since 2006 long term reconstructions of the habitats have been ongoing which strive for the decrease of the invasive woody species on the territory and the insurance of the habitat of the sandy lawn, as well as the long term conservation of the fragments of the lawn and the creation of the natural sandy lawn. This activity is conducted by the volunteers of the MME and with the help of the students of educational institutions in parallel requesting for the permits of the Municipality of the Capital. During these interventions, the shoots were mechanically beat down and they were wiped dried as well. Besides these interventions, it was fundamental to preserve the sensitive, rare or legally protected species and to increase their volume as much as possible.